2020
DOI: 10.1103/physreva.102.052833
|View full text |Cite|
|
Sign up to set email alerts
|

Sensitivity of Th229 nuclear clock transition to variation of the fine-structure constant

Abstract: A nuclear clock has been proposed based on the isomeric transition between the ground state and the first excited state of thorium-229. This transition was recognized as a potentially sensitive probe of possible temporal variation of the fine-structure constant, α. The sensitivity to such a variation can be determined from measurements of the mean-square charge radius and quadrupole moment of the different isomers. However, current measurements of the quadrupole moment are yet to achieve accuracy high enough t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 61 publications
2
37
1
Order By: Relevance
“…The magnetic dipole moment, µ, and the electric quadrupole moment, Q has been obtained by combining our atomic calculation with the measured HFS A B values. We find our determined µ values, 0.359 (9), is in very good agreement with the SDpT results, 0.360 (7). While our electric quadrupole moment, Q = 2.95 (7), is smaller than their recommended value, Q = 3.11 (6), about 5%, owing to the electron correlation represent by the nonlinear terms, which omitted in SDpT calculations, contribute significantly to the electric quadrupole moment and reduce the values.…”
Section: Electronic Octupole Hyperfine Transition Matrixsupporting
confidence: 85%
See 3 more Smart Citations
“…The magnetic dipole moment, µ, and the electric quadrupole moment, Q has been obtained by combining our atomic calculation with the measured HFS A B values. We find our determined µ values, 0.359 (9), is in very good agreement with the SDpT results, 0.360 (7). While our electric quadrupole moment, Q = 2.95 (7), is smaller than their recommended value, Q = 3.11 (6), about 5%, owing to the electron correlation represent by the nonlinear terms, which omitted in SDpT calculations, contribute significantly to the electric quadrupole moment and reduce the values.…”
Section: Electronic Octupole Hyperfine Transition Matrixsupporting
confidence: 85%
“…We found that our CCSD values matched perfectly with the SDpT results 0.360 (7), but lower than other reported results. The comparison of our CCSD result and SDpT result shows that the contribution of the partial triple excitations and the non-linear term on A/µ to the first three states are small.…”
Section: B Magnetic Dipole Momentcontrasting
confidence: 51%
See 2 more Smart Citations
“…A solidstate nuclear clock could be particularly attractive for a space mission. Molecular clocks provide sensitivity to m e /m p variation and a nuclear clock is highly sensitive to hadronic sector, with possible K = 10 4 sensitivity to the variation of m q /Λ QCD [102,111].…”
Section: Atomic Molecular and Nuclear Clocksmentioning
confidence: 99%